An experimental investigation of thermal performance of pulsating heat pipe with alcohols and surfactant solutions. (February 2018) - Bastakoti, Durga; Zhang, Hongna; Cai, Weihua; Li, Fengchen
Highlights: Thermal performance is highly affected by surface tension and viscosity of working fluids. CTAC surfactant as a working fluid in the pulsating heat pipe is advantageous. Influence of thermo-physical properties varies with the fill ratio and heat load condition. Abstract: An experimental investigation was conducted to determine the thermal performance of Pulsating Heat Pipe (PHP) with different concentrations and fill ratios (FRs) of Methanol, Ethanol and Cetyltrimethyl ammonium chloride, C19 H42 ClN (CTAC) and compared with that of Deionized (DI) water. In this study, effects of thermo-physical properties of these working fluids on progression of temperature at different regions of the PHP and thermal resistance at varying thermal loads ranging from 15 W to 80 W were investigated. The closed-loop pulsating heat pipe was bottom heated and kept at vertical position for the entire period of study. 35%, 50% and 65% FRs of DI water were used and it was observed that the thermal resistance was lowest when the PHP was filled with 50% FR. The lowest thermal resistance achieved with DI water was 0.34 K/W at higher heat load. Methanol and Ethanol have lower specific heat capacity and performed almost no better than DI water. Larger (d P /d T )sat values of Methanol and Ethanol produced greater fluctuations in the flow and rapid movement of the fluid was induced within the pipe because of their relatively lower surface tension and viscosity. But these properties were not dominating factors for the thermal performance at higher heat loads. Lower specific heat capacity and latent heat of vaporization of these alcohols dominated the thermal resistance. When 50 ppm, 100 ppm, 1000 ppm and 2000 ppm of CTAC surfactant solutions were used, the experimental results showed that the heat transfer capability of the PHP is highly dependent on FR. It was observed that surface tension and viscosity are dominating factor in the performance of the PHP, when CTAC surfactant solution is used, and their degree of dominance varies with FR and heat loads. Lower surface tension of CTAC solution was advantageous for lower FR and heat load. Lower viscosity offered greater advantage at higher FR and heat load. The lowest thermal resistance achieved with surfactant solution was 0.30 K/W for 35% and 50% FR with 2000 ppm CTAC solution at higher heat load which are lower than that of DI water.